Sexual Education in Indonesia: A Bibliometric Analysis From 1972 to 2022 - Maryani, Ika; Maharani, Ega Asnatasia; Nisaurrahmah; Rahmawati, Siti; Puspitajati, Melati; Ativa, Khansa (Advances in Social Sciences Research Journal, 2022)
This study aims to analyze the scope of sexual education research in Indonesia using bibliometric review. VOSviewer software were used in this study to analyze the number of publications, well-known research topics, author keywords, preferred sources, and country of publication during 1972-2022 period of time. Topic areas with titles, keywords, and abstract criteria in sexual education studies were used as a reference for extracting search results from Scopus database. The search was carried out by the mentioned search terms: “sex” AND “education” AND “Indonesia”. A total of 471 articles were found in Scopus accessed on 24th of June 2022. Results found there was a significant increase in the number of publications from 2019 to 2020. The keyword adult, female, prevalence, middle aged, child, and sex factors turned to be the most widely discussed. This is the first bibliometric review on studies that assessed the significant growth of research on sexual education area, which identified that researchers can directly position research projects on current issues or examine currently relevant innovation opportunities to further develop in this field.